Brief: connecting the carbon and water cycles for systemic resilience - Adolfsson, E. (2025)
The global hydrological cycle is the «bloodstream» of the biosphere, providing the basis for all life, regulating the climate, enabling carbon cycling through the production of biomass, and carrying nutrients, chemicals and pollutants. Freshwater, often overlooked, is the silent currency sustaining our economies — powering every sector from agriculture to energy — and underpinning our livelihoods.